Ixazomib, an oral proteasome inhibitor, exhibits potential effect in dystrophin‐deficient mdx mice. Issue 1 (9th December 2020) - Micheletto, Maria Laura Jorge; Hermes, Tulio de Almeida; Bertassoli, Bruno Machado; Petri, Giuliana; Perez, Matheus Moreira; Fonseca, Fernando Luiz Affonso; Carvalho, Alzira Alves de Siqueira; Feder, David
Abstract: Dystrophin deficiency makes the sarcolemma fragile and susceptible to degeneration in Duchenne muscular dystrophy. The proteasome is a multimeric protease complex and is central to the regulation of cellular proteins. Previous studies have shown that proteasome inhibition improved pathological changes in mdx mice. Ixazomib is the first oral proteasome inhibitor used as a therapy in multiple myeloma. This study investigated the effects of ixazomib on the dystrophic muscle of mdx mice. MDX mice were treated with ixazomib (7.5 mg/kg/wk by gavage) or 0.2 mL of saline for 12 weeks. The Kondziela test was performed to measure muscle strength. The tibialis anterior (TA) and diaphragm (DIA) muscles were used for morphological analysis, and blood samples were collected for biochemical measurement. We observed maintenance of the muscle strength in the animals treated with ixazomib. Treatment with ixazomib had no toxic effect on the mdx mouse. The morphological analysis showed a reduction in the inflammatory area and fibres with central nuclei in the TA and DIA muscles and an increase in the number of fibres with a diameter of 20 µm 2 in the DIA muscle after treatment with ixazomib. There was an increase in the expression of dystrophin and utrophin in the TA and DIA muscles and a reduction in the expression of osteopontin and TGF‐β in the DIA muscle of mdx mice treated with ixazomib. Ixazomib was thus shown to increase the expression of dystrophin and utrophin associated with improved pathological and functional changes in the dystrophic muscles of mdx mice.